MEDIA AUGMENTED REALITY BERBASIS ANDROID DALAM MATERI BANGUN RUANG SISI DATAR SISWA SMP - Ningtias, Ayu; Hartoyo, Agung; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to: (1) Produce a decent learning media in application using Augmented Reality technology based on android of Polyhedron subject and (2) Know student motivation after using the media. This research used Research and Design (R & D) methode. The subjects were VIII I Junior High School 3 Pontianak, include by 37 students. The stages of this research include by analysis, design, development, implementation and evaluation. The result of this research was the media has been categorized as